Bees : their vision, chemical senses, and language - Frisch, Karl von, 1886-1982 (Cornell paperbacks, 1971)
Now back in print after more than two decades, this classic and still accurate account of the behavior patterns and sensory capacities of the honeybee remains a book "written with a simplicity, directness, and charm which all who know him will recognize as characteristic of its author. Any intelligent reader, without scientific training, can enjoy it."--Yale Review